2011
DOI: 10.1021/cb100428c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Specific Inhibitors of Human RAD51 Recombinase Using High-Throughput Screening

Abstract: RAD51 is a key protein of homologous recombination that plays a critical role in the repair of DNA double-strand breaks (DSB) and interstrand cross links (ICL). To better understand the cellular function(s) of human RAD51, we propose to develop specific RAD51 inhibitors. RAD51 inhibitors may also help to increase the potency of anticancer drugs that act by inducing DSBs or ICLs, e.g., cisplatin or ionizing radiation. In vitro, RAD51 promotes DNA strand exchange between homologous ss- and dsDNA. Here, we develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
186
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(198 citation statements)
references
References 30 publications
12
186
0
Order By: Relevance
“…Interestingly, upon differentiation, Rad51 binding to HPV DNA increased per viral genome, suggesting the formation of Rad51 nucleofilaments. To confirm the importance of Rad51 activity in productive viral replication, we utilized the Rad51-specific small-molecule inhibitor B02, which blocks Rad51 binding to DNA and inhibits DNA strand exchange into homologous sequences (47,48). As demonstrated in Fig.…”
Section: Inhibition Of Rad51 Function Prevents Productive Viral Replimentioning
confidence: 99%
“…Interestingly, upon differentiation, Rad51 binding to HPV DNA increased per viral genome, suggesting the formation of Rad51 nucleofilaments. To confirm the importance of Rad51 activity in productive viral replication, we utilized the Rad51-specific small-molecule inhibitor B02, which blocks Rad51 binding to DNA and inhibits DNA strand exchange into homologous sequences (47,48). As demonstrated in Fig.…”
Section: Inhibition Of Rad51 Function Prevents Productive Viral Replimentioning
confidence: 99%
“…Inactivation of these two enzymes or abolition of their interaction could then become a useful strategy to prevent DNA amplification and deletion through HR. In humans, some RAD51 inhibitors were identified by high-throughput screening of the NIH Small Molecule Repository (Ͼ200,000 compounds) (280). Specific RAD51 inhibitors for trypanosomatids could be found by this type of screening.…”
Section: Resistance and Treatmentmentioning
confidence: 99%
“…DNA binding assays revealed that it disrupted initial RAD51 binding to ssDNA, and later dsDNA binding to the RAD51-ssDNA filament 7 . A D-loop assay confirmed B02 specificity for human RAD51 over its bacterial homologue RecA and other human HR proteins 15 . In vitro, B02 inhibited irradiation-induced RAD51 foci formation, HR repair of dsDNA breaks 7 and sensitized cells to a panel of chemotherapy drugs 5,7 .…”
mentioning
confidence: 76%
“…Smaller alkanes (1-4) also displayed reduced activity. Varying spacer length in compound 17, with one methylene unit shorter (15) or longer (16), did not improve activity and indicated optimal positioning of the aromatic ring in 17. Of the substituted benzyl series, fluoro (18)(19)(20), nitro (21-22) and p-hydroxy (23) analogues showed comparable activity.…”
Section: Ar T Ic Le In F O Abstractmentioning
confidence: 97%